Recurrent Mastitis and Its Management in a Secondary Care Hospital: A Case Report - Haridas, Indu Tharayappurath; Babu, Subitha; Basutkar, Roopa Satyanarayan; Ponnusankar, Sivasankaran (Indian Journal of Pharmacy Practice)
Introduction: Mastitis is a painful inflammation of the breast, commonly seen during the lactating period. Case: We present a case of recurrent mastitis of a patient who visited for treatment to a secondary care hospital, Udhagamandalam and describes the treatment strategies followed. The treatment given was found to be in accordance with the world health organization guidelines for treatment of mastitis, Academy of Breast feeding medicine protocol committee, Australia and National treatment guidelines for antimicrobial use in infectious disease (version 1.0, 2016) by the Government of INDIA. The recurrence of mastitis observed in this patient emphasizes the need of educating lactating mothers effectively regarding regular feeding and proper breast feeding techniques, which may enabling them to identify and resolve the predisposing factors of possible breast feeding disorders.
Keywords: Mastitis; Recurrence; Management; Secondary Care; Guidelines